PENGARUH LOCUS OF CONTROL, KOMITMEN ORGANISASI, KINERJA AUDITOR, TIME BUDGET PRESSURE, DAN ETIKA AUDIT TERHADAP PERILAKU DISFUNGSIONAL AUDIT (Studi Empiris Pada Kantor Akuntan Publik di Provinsi Sumatera Barat, Sumatera Utara dan Riau) - Ofita, Nova; Agusti, Restu; Kurnia, Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aimed to examine the effect Locus Of Control,Organizational Commitment, Performance Auditor, Time Budget Pressure, And Audit Ethics To Dysfunctional Audit Behavior. The respondent of this research was the auditor working in Public Accountant Firms in Pekanbaru, Padang, and Medan. The method of collecting data in the research was survey method with the distributing questionnaires. The data usage in this research was primary data collecting through the questionnaires. The questionnaires processed were totaled as many as 50 questionnaires from 80 questionnaires diffused. According to thedata quality consisted of he reliability test , validity test, the and the normality test indicated that all variables could be valid, reliable, and normal so that for the next, the items of every variable concept was appropriately use as an indicator.The result of this research indicated that the audit locus of control variable, performance auditor, time budget pressure, and Audit Ethics have influence to dysfunctional audit behavior. Whilst the organizational Commitment variable don’t have influence to dysfunctional audit behavior.Keywords : Commitment, Performance, Auditor, Ethics and Behavior